2007
DOI: 10.1002/jms.1321
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic selenium speciation in environmental and biological samples by nanometer‐sized materials packed dual‐column separation/preconcentration on‐line coupled with ICP‐MS

Abstract: A novel, fast, and cheap nonchromatographic method for direct speciation of dissolved inorganic and organic selenium species in environmental and biological samples was developed by flow injection (FI) dual-column preconcentration/separation on-line coupled with ICP-MS determination. In the developed technique, the first column packed with nanometer-sized Al(2)O(3) could selectively adsorb the inorganic selenium [Se(IV), Se(VI)], and the retained inorganic selenium could be eluted by 0.2 mol l(-1) NaOH, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
0
24
0
2
Order By: Relevance
“…The regular consumption of tea may contribute to the daily dietary requirements of several essential elements. Considering the enormous consumption of tea and the investigation focusing on selenium, it is necessary to study selenium speciation in tea samples [6]. While there were still nearly few literatures concerning investigation on selenium speciation in tea samples based on high performance liquid chromatography (HPLC) coupled with inductively coupled plasma mass spectrometry (ICP-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The regular consumption of tea may contribute to the daily dietary requirements of several essential elements. Considering the enormous consumption of tea and the investigation focusing on selenium, it is necessary to study selenium speciation in tea samples [6]. While there were still nearly few literatures concerning investigation on selenium speciation in tea samples based on high performance liquid chromatography (HPLC) coupled with inductively coupled plasma mass spectrometry (ICP-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption performance and coexisting ions interference of nanometer‐sized Al 2 O 3 has been evaluated in our previous research works . In the analysis of inorganic and organic Se species by using nanometer‐sized Al 2 O 3 and dimercaptosuccinic acid modified mesoporous TiO 2 packed column, it had been demonstrated that 4 g L −1 K + and Na + , 2 g L −1 Ca 2+ and Mg 2+ , 50 mg L −1 Al 3+ , 10 mg L −1 Fe 3+ , 3 g L −1 NO 3 − and Cl − , 1 g L −1 SO 4 2− , and 50 mg L −1 Br − would hardly affect the recoveries of target Se species . Therefore, only coexisting ions that would affect the CE separation of Se (VI/IV) were considered in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with these low‐cost SPE adsorbents, nanometer‐sized materials are featured with much higher surface area and more activated sites for adsorption due to their unique size and physical properties. In our previous works, the adsorption behaviors of some metal ions on nanometer‐sized TiO 2 and Al 2 O 3 had been systematically studied , and the methods of SPE‐ICP‐optical emission spectrometry (OES)/MS based on nanometer‐sized oxides as adsorbents were established for the determination of trace metals and also speciation analysis of inorganic selenium and seleno amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…Solid phases with these characteristics make possible to build columns with small volume and high retention capacity, which enables in turn the determination of the analyte at trace levels, and using low volumes of eluent and wastes. Thus, micro-and mini-columns packed with nanometersized materials have been used for speciation of dissolved inorganic and organic Se species [20], simultaneous determination of trace metals (V, Cr, Mn, Co, Ni, Cu, Zn, Cd and Pb) [17]. Moreover, nanostructured TiO 2 has been employed for speciation of Cr(III) and Cr(VI) in environmental samples [21,22].…”
Section: Introductionmentioning
confidence: 99%